Elections and impeding democracy – Astudy in the Iraqi case for 2018 - Muhammad, Tara Omer; Majed, Dlawar Othman (Journal of Legal and Political Studies, 2021)
Elections are democratically credible when they are implemented along with specific benchmarks rendering them characterized by freedom, integrity, justice and effectiveness which constitute the basic mechanism for backing the political system democracy as in societies with established democracies. This is because they are considered an outcome of the people's will through competition between political forces and blocs with diverse programs and opposing ideas and interests aimed at accomplishing the best interest for all within the periodic improvement of the public’s choice. This is to stamp a distinct mark on the system of government and society. Elections cannot play their anticipated role if they are not equipped with required settings to succeed. These conditions can be achieved by finding solutions to both a series of interconnected, integrated and accumulated internal legal and political quandaries, and some economic, social, cultural and security areas. In addition, there must be solutions to transitory outside quandaries which create challenges and negative impacts, and accordingly impede the exercise of democratic elections as a basic mechanism for building a democratic state. Frequently, in societies shifting these quandaries overlap with the conditions of an ideal democracy which make elections an impediment to democracy, not vice versa. To cite an evidence for this case, the 2018 Iraqi election is a realistic model. If the associated shortcomings and breaches of the mentioned election are examined in details, one can realize the extent of the impact of these disparities on the nonexistence of the essential basis for the conduct of the election. Consequently, the concept of democratic elections and the standards and measures for conducting them are examined in this study to evaluate it in light of the imbalances that are inconsistent with the ones presented in the Iraqi September 2018 election case and experience.
Keywords: Elections; Democraticy; Freedom; Integrity; Justice; Iraq